Legal regulation of personal data taking into account the use of ID-cards and biometric passports - Ablameyko, Maria S. (Journal of the Belarusian State University. Law, 2019)
In this paper international acts and laws of some countries on the protection of personal data are analyzed. The main points of the existing legislation of the Republic of Belarus in this sphere are considered. It is suggested what the main points should be reflected in the forthcoming law. Special attention is paid to the introduction of ID-cards and biometric passports in 2019. The new law should comprehensively regulate the issues of legal regulation and protection of personal data.
Keywords: protection of personal data; ID-cards; biometric passports